Novel KhÄn Al-KhalÄ«lÄ« Karya NajÄ«b MachfÅ«zh: Analisis Psikologi Humanistik Abraham Maslow - Irawati, Retno Purnama (LP2M IAIN Palangka Raya, 2009)
Â The main problems of this study as follows: how the character and the psychological problem were dealt by the main leading figure in this novel and how the leading figure managed and solved the problems. Moreover, how the life of the writer especially when the writer wrote this novel and whether the psychological problems that was dealt by the lead figure of this novel is the represent of the writerâs or other people. The objectives of this research are (a) to reveal the character and psychological problem of the leading figure using the approach of Abraham Maslowâs Humanistic Psychology, (b) analyzed the life of the writer especially when the writer wrote this novel, and (c) to make the readers aware that the personal maturity of someone did not come only from the psychological development of the relevant person, but really regarding to the outside condition of himself.To answer the above problem, the data was gathering from the material object of the research that is the novel by NajÄ«b MachfÅ«zh entitled KhÄn Al-KhalÄ«lÄ«. The lead figure in this novel is as the main subject. This research used two methods that is analyzing the life of the writer to understand his work and analyzing the character of the available leading figure in the literary work. Furthermore, to analyze the data, using the Abraham Maslowâs humanistic psychology theory, that is needs hierarchy theory and self-actualization theory that include inside is the definition and characteristic of mental illnesses, in this case neurosis.The result of the research shows that the character of Ahmad âÄkif AfandÄ« has series of psychological problems that guided him to become neurotic personality. This personality formed him into the character of inability to seize the reality efficiently, being paralyzed by the embarrassed feeling, could not have a spontaneous attitude, failed to develop his interest and talent, emerged anger on the love that was lost, lost the safe feeling, focused on himself only, and could not function autonomously. Moreover, the traumatic problem which continuously appear, the often failure in gaining the goal and the love, as well as the failure in the fulfillment of basic need and metaneeds has also became the initiator of the growth of neurotic personality in Ahmad âÄkif.Â